Analysis of the Implementation of Teaching Factory Development by Using the Critical Path Method - Trisna - Mesra (UIN Sultan Syarif Kasim Riau, 2021)
A project is a unique series of interrelated activities to achieve a certain result and carried out within a certain period of time. However, most projects are implemented not using proper and appropriate management, so that it has an impact on wasting time and project budget costs which causes low profits for contractor companies.Based on these problems, the authors conducted research using the CPM (Critical Path Method) method in order to find the optimal time in project implementation and to obtain optimal budget costs in implementing the Teaching Factory development project at SMKS Taruna Persada Dumai. In addition, this study also uses CV (Cost Variance) and SV (Schedule Variance) to determine the performance index and project performance. Based on calculations through the CPM (Critical Path Method) method, the optimal time for the implementation of this project is 65 working days, with the optimal cost based on the CPM (Critical Path Method) calculation obtained a cost of Rp. 188,044,781. Based on the calculation of performance through the CV (Cost Variance) and SV (Schedule Variance) methods, the Teaching Factory project obtained a CV value of -Rp. 4,949,624 and the SV value of Rp. 7.398.376. This states that the Teaching Factory development project in terms of work implementation is faster than planned with the costs spent being greater than budgeted.